1990
DOI: 10.1002/art.1780330514
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies, ly‐1, and immunoglobulin v gene expression in hybridomas obtained from young and from old new zealand black mice

Abstract: We obtained a large number of hybridomas from l-month-old and 16-month-old New Zealand black mice to study the fine specificities of the autoantibodies produced, the expression of Ly-1, and the expression of the immunoglobulin V gene families in this autoimmune strain. Analysis of the autoantibody specificities yielded 2 major classifications: those specific for a single autoantigen and those that exhibited multispecific binding. Among the multispecific antibodies, 2 categories were found: an antigen-inhibitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A high proportion of clones specific for DNA were obtained from normal mice [88], but multi-reactive hybridomas were found to be equally frequent in NZB mice and in mice not prone to auto-immunity [89]. In one report [90], monospecific anti-double stranded (ds)DNA antibodies were claimed to be relatively frequent in young and old auto-immune mice and, furthermore, clones that displayed specificities devoid of detectable self-reactivity, found to be of the CD5+ and conventional B cell phenotypes. Taken together, these data raise the important question as to whether autoantibodies produced by CD5+ B cells from both patients or auto-immune strains of mice, differ from auto-antibodies secreted by CD5+ B cells from normal individuals or mice not prone to autoimmunity.…”
Section: Production Of Auto-antibodiesmentioning
confidence: 99%
“…A high proportion of clones specific for DNA were obtained from normal mice [88], but multi-reactive hybridomas were found to be equally frequent in NZB mice and in mice not prone to auto-immunity [89]. In one report [90], monospecific anti-double stranded (ds)DNA antibodies were claimed to be relatively frequent in young and old auto-immune mice and, furthermore, clones that displayed specificities devoid of detectable self-reactivity, found to be of the CD5+ and conventional B cell phenotypes. Taken together, these data raise the important question as to whether autoantibodies produced by CD5+ B cells from both patients or auto-immune strains of mice, differ from auto-antibodies secreted by CD5+ B cells from normal individuals or mice not prone to autoimmunity.…”
Section: Production Of Auto-antibodiesmentioning
confidence: 99%
“…The method of Manser and Gefter (15) was used to identify BALB/c-derived hybridomas expressing the VHX-24 gene family and NZB-derived hybridomas expressing the VK1 gene family, as described (16,17). All positive BALB/c lines and 18 randomly selected NZB lines were cloned by limiting dilution and rescreened under high-stringency conditions.…”
Section: Methodsmentioning
confidence: 99%
“…This was demonstrated by immunofiuorescence staining of the hybridomas for cytoplasmic CD5. Fidanza et al [21] have recently reported that hybridomas derived from CD5 B lymphocytes, which normally lose expression of surface CD5 during the fusion with the myeloma cell line, retain cytoplasmic expression of the CD5 antigen. By detecting the expression or non-expression of cytoplasmic CD5 in our eight anti-mouse erythrocyte MoAbs we have been able to identify the cellular origin of these hybridomas (whether derived from CD5+ or CD5" B lymphocytes) (Sadigh et al, manuscript submitted).…”
Section: Dtscusstonmentioning
confidence: 99%